Dissertation to published article: A journey from shame to sharing - McPherson, Alan (European Journal for Qualitative Research in Psychotherapy, 2020)
This paper describes my experiences of re-presenting my research from a master’s degree in Integrative Psychotherapy into a paper suitable for publication in a peer-reviewed journal. Bringing together two different approaches in qualitative research: autoethnography and reflexivity, I reflect on my personal journey of creating an article for publication and becoming a researcher-practitioner. I offer two ‘voices’ represented by the literary device of different fonts: the first offers a more factual, neutral, information-giving account; the second is more subjective where I expose my emotional responses at the time and now. This paper highlights the wider challenges and personal obstacles of becoming published within the field of counselling and psychotherapy. My hope is that it will inspire other graduates to consider taking the final step to re-present their research from their degrees and share their participant’s stories within the counselling and psychotherapy community, and beyond.